Development of a novel chemiluminescence method for the determination of cefazolin sodium in injectable powder and human urine based on a luminol‐Cu(III) complex reaction in alkaline medium. (15th July 2012) - Sun, Hanwen; Wang, Juan; Wang, Ting
ABSTRACT: A novel chemiluminescence (CL) method was developed for the determination of cefazolin sodium based on the CL reaction between the [Cu(HIO6 )2 ] 5‐ Cu(III) complex and luminol in alkaline solution. Results showed that CL emission of Cu(III) complex–luminol in alkaline medium was significantly different from that in acidic medium. A possible mechanism of the enhanced effect of cefazolin on CL emission of the [Cu(HIO6 )2 ] 5‐ ‐ luminol system was proposed. The effect of the reaction conditions on CL emissions was examined. Under optimized conditions, a good linear relationship was obtained between CL intensity and concentrations of cefazolin sodium in the range of 2.0 x 10 ‐8 to 2.0 x 10 ‐6 g/mL with a correlation coefficient of R 2 = 0.9978. The limit of detection was 4.58 x 10 ‐9 g/mL. The proposed method was applied for the determination of cefazolin sodium in real samples with recoveries of 82.0‐109% with an RSD of 0.7‐2.1%. The proposed method was successfully used for the determination of cefazolin sodium in injectable powder preparations and human urine with satisfactory results. Copyright © 2012 John Wiley & Sons, Ltd.